“RUBBISH” VS. “BUYER BE AWARE”: A Cross-Cultural Move Analysis of Chinese and American Negative Online Shopping Reviews and Their Corresponding Responses (Sinología hispánica. China Studies Review, 2020)
The present study aims at comparing the move structures of Chinese and American negativeonline shopping reviews and managerial responses, and the influence of negative online reviews on peercustomer. The researchers collected 158 Chinese negative shopping reviews from www.jd.com, followedby 157 managerial responses and 76 peer customer responses, and 156 American negative reviews fromwww.amazon.com, followed by 139 managerial responses and 97 peer customer responses, respectively.The negative online reviews were analyzed into explicitly-impolite and implicit-impolite moves, themanagerial responses were analyzed into rapport-enhancing and rapport-damaging move, and the peercustomer responses were analyzed into agreement and disagreement with the negative online reviews.After qualitative analysis, the researchers conducted chi-square to examine whether the differencesbetween the Chinese and American negative online reviews and managerial and peer customer responseswere significant of not. The results show that the American negative online reviewer has matured as agenre, in that American negative online reviewers not only criticized the commodity, service, etc., butalso warned other customers against making the purchase, while Chinese negative online reviews mainlyaimed at criticizing the commodity, services, etc., leaving the decision to the peer customer. In termsof managerial responses, the Chinese manufacturer responded significantly more to the negative onlinereviewer, but employed more rapport-damaging moves than their American counterpart. By contrast,the American manufacturer customized their greeting and rectification with a unique reference code,which make their managerial responses more individualized. As for peer-customer responses, the resultsshow that negative online reviews had a greater impact on Chinese peer customers than their Americanequivalents. The findings may provide directions for the Chinese and American negative reviewers andthe management to adjust their move structures of negative reviews and managerial responses to thenegative online shopping reviews according to target consumers.